Peran Intervensi Disiplin Kerja dalam Hubungan Motivasi Kerja dan Lingkungan Kerja Fisik terhadap Kinerja karyawan - Deswita Tazlia; Wawan Prahyawan; Ika Utami Widyaningsih (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to determine the role of Work Motivation (X1) and the Physical Work Environment (X2) on Employee Performance (Y), with Work Discipline (Z) as an Intervening Variable. The research method used was quantitative, with data collection based on questionnaires and literature review. The population in this study were employees of PT. Tunas Alfin Plant 2 Cikupa. The sample size was 75 respondents, drawn using nonprobability sampling, i.e., saturated sampling. The data analysis method used was Structural Equation Modeling (SEM) with the analysis tool SmartPLS 4.0. This study found that Work Motivation (X1) had a positive and significant effect on Employee Performance (Y). The Physical Work Environment (X2) had a positive but insignificant effect on Employee Performance (Y). Work Motivation (X1) had a positive and significant effect on Work Discipline (Z). The Physical Work Environment (X2) had a positive and significant effect on Work Discipline (Z). Work Discipline has a positive and significant effect on Employee Performance (Y). Work Discipline mediates Work Motivation (X1) and Employee Performance (Y), and Work Discipline mediates the Physical Work Environment (X2) and Employee Performance (Y).